Implementation of a Multi-Agent in a Virtual Maze - Hernández Camacho, Rocio C.; Hernández Camacho, Jorge (Ciencia Huasteca Boletín Científico de la Escuela Superior de Huejutla, 2014)
This paper presents a Multiagent System (SMA) that controls the morphological status of the graphical user in a 3D virtual world where interaction takes place between the user and the system. The agents of this system can sense the 3D virtual world and represent the result of the deliberation of the SMA in the virtual world.